Exercise technique: hexagonal bar romanian deadlift - Snarr, R. L.; Adams, K.; Cook, J. (Strength and Conditioning Journal, 2021)
This column provides a description of the correct technique for a hexagonal bar Romanian deadlift (RDL). The use of the hexagonal bar provides a unique variation of the conventional RDL to promote a more advantageous upright body posture, thereby allowing greater loads to be lifted and reductions in spinal compression forces. Additionally, the use of the hexagonal bar RDL can aid in the development in the musculature of the posterior chain benefiting those who are required to sprint and jump regularly.